Method for Detect and Extract Forgery from Images (مجلة المنصور, 2022)
According the availability of many image editing and processing tools, it is led possible to easily change the information represented by a digital images without leaving any obvious traces of tampering, which led to the problem of verification image. These issues of multimedia security have led to the development of several approaches to tampering detection. Digital image forensics is branch that deals with the identity and authenticity of the images. The proposed system is the Verification system for images. Where the Verification system used non-blind passive image forensic, and that it has been achieved by using fuzzy gradient based image reconstruction, which is able to detect and extract all types of forgery (Splicing, Image Retouching, Geometrical Transformation, Copy Move Attack, other type) and also able to compute forgery ratio as percentage. The experimental results show that the proposed system achieves accuracy of 100% for detect and extract all type of forgery, with image enhancement capabilities.